Infant feeding, poverty and human development - Amir Lisa H; Beasley Annette (BMC, 2007)
Abstract The relationship between poverty and human development touches on a central aim of the International Breastfeeding Journal's editorial policy which is to support and protect the health and wellbeing of all infants through the promotion of breastfeeding. It is proposed that exclusive breastfeeding for 6 months, followed by continued breastfeeding to 12 months, could prevent 1,301,000 deaths or 13% of all child deaths under 5 years in a hypothetical year. Although there is a conventional wisdom that poverty 'protects' breastfeeding in developing countries, poverty actually threatens breastfeeding, both directly and indirectly. In the light of increasingly aggressive marketing behaviour of the infant formula manufacturers and the need to protect the breastfeeding rights of working women, urgent action is required to ensure the principles and aim of the International Code of Breastmilk Substitutes, and subsequent relevant resolutions of the World Health Assembly, are implemented. If global disparities in infant health and development are to be significantly reduced, gender inequities associated with reduced access to education and inadequate nutrition for girls need to be addressed. Improving women's physical and mental health will lead to better developmental outcomes for their children.